Alteration of Behavioral Inhibitory Control in High-Altitude Immigrants - Wang, Jiazheng; Zheng, Liqin; Wang, Zedong; Wu, Xiao; Ma, Ning; Zhang, Tao; Chen, Kai; Biswal, Bharat B.; Yang, Qun; Ma, Hailin (Frontiers in Behavioral Neuroscience, 2021)
Behavioral inhibitory control (BIC) is essential for enabling humans to withhold inappropriate behaviors and live adaptively in changing environments, especially in extreme situation of high-altitude environment; Hypoxia, a major symptom at high-altitude, can induce astrocytic release lactose, the major energy source for the neurons. However, it is not clear whether long-term exposure to high-altitudes may affect an individual’s BIC. To clarify the role of altitude in adults’ behavioral control and the underlying neural mechanism, we explored the BIC neural activity profiles of healthy immigrants from high-altitude regions. Combining a two-choice oddball paradigm and electrophysiological techniques, the current study monitored the N2 and P3 event-related components and neural oscillations across low-altitude (LA) and high-altitude (HA) groups. Results showed longer reaction times for the HA than LA group. Relative to LA group, lower N2 and P3 amplitudes were observed for the HA group. Significant positive correlations were also found between P3 amplitude and theta/delta band power across both groups. Importantly, lower theta/delta band powers were only observed for the HA group under deviant condition. Collectively, these findings suggest that long term exposure to high-altitudes may attenuate BIC during response inhibition stage and provide valuable insights into the neurocognitive implications of environmental altitude on BIC.